Road development and Indigenous hunting in Tanah Papua: Connecting the facts for future wildlife conservation agendas - Pattiselanno, Freddy; Krockenberger, Andrew (Forest and Society, 2021)
Road development is increasing worldwide. Generally, examples of road building in tropical countries demonstrate that road access can assist the fight against rural poverty, but such developments are also linked to deforestation, pollution, invasions of exotic species, and environmental degradation. For Papua and West Papua provinces (Tanah Papua) in Indonesia, the development of the provincial road network is intended to improve the rural economy, aiming to alleviate poverty within isolated rural areas. However, road development can pose particularly challenging problems to rural and Indigenous communities. Poorly planned roads can be devastating when they provide easy access to illegal hunting that threatens endangered species. In this study, we discuss how road development in Tanah Papua has changed indigenous hunting. Native Papuans have benefited from improved road access, which allows them to sell their agricultural products at local markets. Increased road connectivity has also changed how local people use natural resources and forest products, moving from subsistence to a more market-based orientation. Although policies on infrastructure development including roads form part of Indonesia’s national program, they are not automatically compatible with a sustainable development program in Tanah Papua. To foster more equitable and sustainable road development, government agencies must improve their overall coordination of further road expansion plans by promoting green infrastructure that supports the sustainable use of natural resources in a way that is reconciled with traditional knowledge of local people. Such efforts may also have positive effects on the efforts to protect biodiversity within the wider government conservation agendas.